Genuine Global Governance: Hegemony to Legitimacy. (March 2014) - Babu, B. Ramesh
Revolutionary changes sweeping the world since the mid-1980s have transformed international and global politics. Major issues and challenges confronting mankind have become global and demand global solutions. However, present international institutions are out of tune with today's realities. Reforms will not do. New forms of global governance are needed. This is an opportune time for the Global South (Third World) to rise to the occasion and offer viable alternative conceptions of global governance that are more cooperative, inclusive, equitable and legitimate. Towards this end, mankind has to draw from all the living civilisations on earth and formulate a 'confluence of cultures' as the conceptual foundation for 'genuine global governance'. Mankind needs a new 'philosophy of globalism'. In this context, Hindu civilisation's ideas on the rights and duties of man; man's relationship with his family, community and society; his place on earth; and its emphasis on living in tune with nature deserve attention.